EXPLORING THE CRITICAL ROLE OF NURSES IN THE PALLIATIVE CARE. - Nasser Dakhilallah Alrashidi, ‏Abdullah Maayouf Alanezi, ‏Nawal Ali Alshaikhahmad, ‏Fatimah Abdullah Asiri, ‏Mohmmad Ahmed Mohmmad Alzhrani, ‏Mutabmarshoobalkareeni,,; Mohammed faleh Al Muteri, ‏Turki Mohammed Alsahli, ‏Huda Abdullah Alqurashi, ‏Lueife Ali Eid Al Rashedi, ‏Norah Mawaad Rubaian Alrashidi, Raid Azem Al Dawsary, Wafa Bashar Alruwaili, Ali Yahya Alqahtani, Zahra Ali Hazazi, (Chelonian Research Foundation, 2022)
Palliative nursing care is a multifaceted strategy to address the medical, psychological, social, and spiritual needs of patients with terminal illnesses. This essay looks at several facets of providing palliative care, from the necessity of creating palliative care services in primary care settings to the critical function community nurses have in providing individualized home care. It explores the intricacies of managing symptoms, tackling typical physiological and psychological indications such discomfort, exhaustion, nausea, worry, and sleeplessness. In addition, the talk delves into ethical issues surrounding palliative care, emphasizing how crucial it is to preserve values like beneficence, autonomy, and advocacy when making decisions. The topic of family engagement in caring is also covered, with a focus on the importance of clear communication, education, and support in order to protect the health of patients as well as their loved ones. Moreover, the necessity of ongoing education and having access to trustworthy resources is highlighted by the integration of evidence-based methods into nursing care. Through the adoption of a comprehensive strategy, the prudent handling of moral quandaries, and the promotion of cooperation among patients, families, and multidisciplinary teams, nurses can maintain the best possible standards of care for those facing the end of their life. This essay seeks to shed light on the intricacies of palliative nursing care and emphasize the value of person-centered, compassionate assistance in improving the quality of life for those with terminal diseases. Key words: Nursing, Palliative care, medical care, pain management, evidence-based.